THE RELATIONSHIP OF TEACHERS' ONLINE MANAGEMENT SKILLS, INNOVATIVE ABILITY, AND PARENTAL SUPPORT WITH LEARNING INTERESTS OF FIFTH GRADE STUDENTS - Zein Nawawi; Abdul Khamid; Ruwandi Ruwandi (Universitas Muhammadiyah Metro, 2021)
Education is an inseparable part of the whole of human life. Because the means to obtain a decent human survival as well as part of human rights in the process of preparing oneself for a better future is through education itself. This study aims to find and analyze the relationship between teacher skills in managing online learning and the ability to innovate with students' interest in learning through parental support as an intervening variable for fifth grade students at SDN Karangjati 04. This type of research uses quantitative research, with a sample of 30 students. While the method of collecting data is through a questionnaire, then the data is analyzed using statistical analysis with multiple regression analysis, path analysis and Sobel test. Based on the results of research at SDN Karangjati 04 Kec. Bergas, Kab. Semarang shows that there is no significant relationship between teacher skills in managing online learning and the ability to innovate on students' interest in learning with parental support as an intervening variable. This is because the value of the direct relationship between the teacher's ability to manage online learning is 0.039 and the indirect relationship through mediation of parental support is 0.0380 which means that the value of the indirect relationship is smaller than the value of the direct relationship and the significance value is 0.862 more than 0.050.Keywords: Teachers Online Management, Parental Support Learning, Learning Interest